2010
DOI: 10.3945/ajcn.2009.28686
|View full text |Cite
|
Sign up to set email alerts
|

Twelve weeks of moderate aerobic exercise without dietary intervention or weight loss does not affect 24-h energy expenditure in lean and obese adolescents

Abstract: Background: Exercise might have a persistent effect on energy expenditure and fat oxidation, resulting in increased fat loss. However, even without weight loss, exercise results in positive metabolic effects. The effect of an aerobic exercise program on 24-h total energy expenditure (TEE) and its components-basal (BEE), sleep (SEE), and awake sedentary (SEDEE) energy expenditure and substrate oxidation-has not been studied in lean and obese adolescents. Objective: The objective was to test the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
3
0
3
Order By: Relevance
“…Van Der Heijden et al 21 evaluó el gasto energético y sus componentes en adolescentes obesos, incluyendo la TMR, observando que después de 12 semanas de entrenamiento aeróbico realizado cuatro veces por semana, y tampoco existió un aumento de la TMR evaluada 38 horas después de la última sesión de ejercicios. Según Van Der Heiden et al 21 , el escaso incremento en la masa magra corporal producido por el entrenamiento (2-3%) fue insuficiente para afectar el gasto energético. Para Alberga et al 25 , es necesario un gran aumento en la masa muscular para producir una elevación significativa de la TMR.…”
Section: B) Ejercicio Aeróbico Y La Tasa Metabólica En Reposounclassified
See 2 more Smart Citations
“…Van Der Heijden et al 21 evaluó el gasto energético y sus componentes en adolescentes obesos, incluyendo la TMR, observando que después de 12 semanas de entrenamiento aeróbico realizado cuatro veces por semana, y tampoco existió un aumento de la TMR evaluada 38 horas después de la última sesión de ejercicios. Según Van Der Heiden et al 21 , el escaso incremento en la masa magra corporal producido por el entrenamiento (2-3%) fue insuficiente para afectar el gasto energético. Para Alberga et al 25 , es necesario un gran aumento en la masa muscular para producir una elevación significativa de la TMR.…”
Section: B) Ejercicio Aeróbico Y La Tasa Metabólica En Reposounclassified
“…Si se pretende analizar el efecto crónico del entrenamiento, habría que conocer el tiempo exacto de recuperación para una sesión de ejercicios y así excluir el efecto agudo de la última sesión que haría sobreestimar el efecto del período de entrenamiento en la TMR. En la mayor parte de los estudios 14,19,21,22 que no encuentran efecto del entrenamiento en la TMR, éste se evaluó a partir de las 24 horas después del último ejercicio aeróbico. Ese puede ser un error metodológico importante, pues el proceso de aceleración de la TMR suele ocurrir inmediatamente después del ejercicio, descendiendo a lo largo de las primeras cuatro horas, hasta llegar a los niveles de normalidad en un periodo de tiempo inferior a las 24 horas.…”
Section: B) Ejercicio Aeróbico Y La Tasa Metabólica En Reposounclassified
See 1 more Smart Citation
“…A secondary analysis of data collected in the GameBike trial (1) showed marginal decreases in EI in response to a 10-week PA programme (46). The two available studies examining exerciseinduced changes in total energy expenditure (TEE) reported no evidence of compensatory behaviours (9,51). When chronic compensatory behaviours in adolescents with obesity are considered, a meta-analysis of nine physical activity interventions, ranging from 3 to 12 months in duration, concluded that PA interventions favour a reduction in EI in this population but reiterated the clear need for further empirical research to confirm this finding (37).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining physical active is vital to attain energy balance. In the past, many weight‐control interventions have been focusing on promotion of sports participation and combating sedentary behaviours (2–4). More sedentary lifestyles in adolescence could lead to overweight or obesity (5,6).…”
Section: Introductionmentioning
confidence: 99%